Experimental comparative evaluation of a graphene nanofluid coolant in miniature plate heat exchanger - Wang, Zhe (2020)
As a novel coolant, the ethylene glycol-water (50 wt.%:50 wt.%) with graphene nanoplatelets nanofluids (GnP-EGW) were prepared at four weight concentrations (0.01, 0.1 0.5 and 1.0 wt.%), and heat transfer and pressure drop characteristics in a miniature plate heat exchanger (MPHE) were investigated. All nanofluid samples were prepared and diluted by ultrasonic vibration, and their thermal conductivity and dynamic viscosity were measured by a transient plane source method and a rotational rheometer, respectively. Firstly, the convective heat transfer coefficient (HTC) and pressure drop correlations were predicted under the condition that water was employed as working fluid in both the hot and cold sides of the MPHE. Then, the effects of GnP concentrations of nanofluids on the thermal and hydraulic performances have been determined for the MPHE with the nanofluid in hot side and the water in cold side. Parametric evaluation and performance comparison of the MPHE using GnP-EGW were analyzed via various operating conditions. Experimental analysis showed that: the proposed correlations from water can predict the experimental data of the base fluid and GnP-EGW nanofluids. In the proper concentration range from 0.01 to 0.1 wt.%, the GnP-EGW nanofluid has an acceptable pressure drop penalty but a higher heat transfer performance compared with the base fluid in the MPHE, which reveals that it might be a potential cooling medium.